Concept of 'bad death' - Marija Vučković (University of Belgrade, 2016)
Following previous research on the linguistic concept of а 'bad death' which lexical expression is the word family of the verb ginuti, I focus my attention in this paper on the relationship between language conceptualization of а 'bad death' and the representation of а 'bad death' in traditional and contemporary culture. Diachronically based language corpus makes possible to trace the changes of referential frame and use of verb ginuti and its derivatives. In the traditional culture а 'bad death' is marked in action code by irregular way of burial and beliefs in demons stemming from the 'impure dead'. In the paper I explore the degree of synonymy of the symbols of all three codes: verbal code, action code and code of beliefs. In the contemporary culture the lack of individual control and choice is considered to be the key element of the concept of a 'bad death'. This change of conceptual content manifests itself in the use of its lexical expressions.